Application of Cooperative Learning Model Teams Games Tournament (TGT)Type to Increase Activity and Results of Biology Learning in Class X-MIA 2, MAN-1 Pekanbaru 2015-2016 Academic Year - Istiqomah, Istiqomah (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Student learning result of class X MIA-2 MAN-1 Pekanbaru still not satisfactory. The strategies and methods used by teachers have not been able to improve the learning outcomes of students Biology subjects. So that, it is necessary to improve the activity and learning outcomes of students through the implementation of cooperative learning Teams Games Tournament Type. The purpose of this study is, to describe the influence of the application of cooperative learning Teams Games Tournament Type seen from the student activities and learning outcomes on the subjects of Biology, The topic is about Plantae in class X MIA-2 MAN-1 Pekanbaru. This Research Type is Classroom Action Research, That is Reflective Research by behavior of action done by teacher to improve learning process, consist of 2 cycles. Each cycle consists of planning, execution, observation and reflection. Assessment instruments in this research is, form of student worksheets, and discussion activity Sheets. The results showed that Cooperative Learning Type Teams Games Tournament (TGT) can improve student activities and learning outcomes. Student activity in firstcycle is 66,66 % (24 student succes) increase become 75 % ( 27 student succes ) in cycle 2. While student learning outcomes increased from 69.44% in the first cycle to 80.55 on cycle 2. The conclusion of this study is Cooperative Learning Teams Games Tournament (TGT) can increase the activity and learning outcomes Biology class X-MIA 2 MAN-1 Pekanbaru Academic Year 2015-2016.